Ecological Impacts of Untreated Chicken Manure on Soil Health of a Few Poultry Farms in Osun State, Nigeria (Global Journal of Science Frontier Research, 2025)
The present work attempts to determine soil sustainability by recognizing the impact of untreated chicken manure on soil health status by applying the fertility content method in various site usages in a few poultry farms in the Osun State, Nigeria. Nearly all of the chicken manure generated in advanced countries is treated before application, while in growing countries chicken manure treatment is insignificant. Untreated chicken manure soil samples were collected from poultry, arable land, and bush fallow, while forestland sites were served as control. The chemical, primary, and secondary variables were determined utilizing standard procedures, while minor nutrients contents were performed with Flame Atomic Absorption Spectrophotometer after wet acid digestion.
Keywords: land usage activities; untreated chicken manure; chicken sustainable management; soil health status; fertility content